Effect of hybrid aluminum dihydrogen phosphate on the corrosion resistance of PTFE composite ceramic coatings. Issue 1 (3rd August 2021) - Wang, Jianyu; Bian, Da; Zhao, Yongwu; Liu, Yaxuan; Liu, Yang
Abstract: In this study, the polytetrafluoroethylene (PTFE) composite ceramic coatings with hybrid aluminum dihydrogen phosphate (AP) are prepared on AISI 304L stainless steel by spraying and heat curing to improve the corrosion resistance of the coatings. AP is hybridized with methyltriethoxysilane (MTES), and the structure of the hybrid AP is characterized by Fourier‐transform infrared spectroscopy and X‐ray photoelectron spectroscopy. Contact angle tests, scratch tests, and electrochemical experiments are used to investigate the corrosion behavior of composite ceramic coatings. In addition, scanning electron microscopy is used to examine the microscopic morphology of the coatings after corrosion to investigate the mechanism of the hybrid AP on the corrosion resistance of the composite ceramic coatings. The findings reveal that MTES successfully hybridizes with AP and implants the –CH3 hydrophobic group in AP, which improves the hydrophobicity of composite coatings. The corrosion potential of hybrid AP coatings all move in a positive direction, and the corrosion current density is lower than that of unhybridized AP coatings. The corrosion current density of the coating is about 2.931e−008 A/cm 2 when the MTES content is 5 wt%, which is 20% less than that of the unhybridized AP coating. Results indicate hybrid AP can significantly improve the corrosion resistance of PTFE composite ceramic coatings with the best corrosion resistance occurring when the content of MTES is 5 wt%. Abstract : The effect of hybrid aluminum dihydrogen phosphate (AP) on the corrosion resistance of polytetrafluoroethylene (PTFE) composite ceramic coatings is investigated. The –CH3 group in the hybrid AP and the –CF2 group in the PTFE work synergistically to improve the hydrophobicity of the coating. The organic–inorganic three‐dimensional mesh structure can well disperse ceramic particles and improve the denseness of the coating.